The Issues Related to the Translation of Social Science Essays About Native Peoples in Québec - Patricia Raynault-Desgagné (Recherches amérindiennes au Québec, 2020)
This article deals with the issues that were raised during the translation of Toby Morantz’ text about the James Bay Crees, published in 2002 by McGill-Queen’s University Press. The challenges met during the exercise of translating this text raised broader issues related to the translation and publication of anthropological works about Native Peoples in Québec. First, this article will identify some contextual elements, notably surrounding the editorial world that could help explain the very low number of translated works about First Nations, highlighting the symbolic capital attributed to the various stakeholders involved in these kinds of publications and to the subject of study. This article will then discuss the issues related to the actual translation of an anthropological text in this postcolonial era. Is it possible and desirable, in the current editorial context in Québec, for Eurocanadian anthropologists, like the author of this article, to take part in the « decolonization » of history through the translation of ethnohistoric texts? Cet article porte sur les enjeux traductologiques qui se sont posés lors de l’exercice de traduction du texte de Toby Morantz sur les Cris de la Baie-James, paru en 2002 chez McGill-Queen’s University Press. Les défis auxquels la traductrice a été confrontée l’ont amenée à se questionner de façon plus large sur les enjeux associés à la traduction et à la publication d’ouvrages anthropologiques portant sur les Autochtones au Québec. Dans un premier temps, cet article tente d’identifier certains éléments contextuels, notamment le contexte éditorial, qui permettraient d’expliquer la faible quantité de traductions d’ouvrages portant sur les Premières Nations et mettant en perspective le capital symbolique relatif des différents acteurs concernés par ce genre de publications ainsi que par ce sujet d’étude. Dans un deuxième temps, l’article aborde les enjeux associés à la traduction en soi d’une oeuvre anthropologique en cette ère postcoloniale. Est-il possible et souhaitable, ...